2017
DOI: 10.1039/c6ta07592d
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the electronic bands of WO3/BiVO4/TiO2, revealing high solar water splitting efficiency

Abstract: In photoelectrochemical (PEC) water splitting, heterojunction electrodes consisting of two or more dissimilar semiconductors offer more advantages over those made from single semiconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…[130] with permission from Elsevier. [143] This study reveals that the formation of ap -n junction at the interface allows better charge separation. [138,139] Ar ecent report by Singh et al sheds light on the band engineering of TiO 2 :BiVO 4 ,w hich predicts at ransition from the type Ia lignment to the most efficient type II alignment.…”
Section: Heterojunctionmentioning
confidence: 71%
“…[130] with permission from Elsevier. [143] This study reveals that the formation of ap -n junction at the interface allows better charge separation. [138,139] Ar ecent report by Singh et al sheds light on the band engineering of TiO 2 :BiVO 4 ,w hich predicts at ransition from the type Ia lignment to the most efficient type II alignment.…”
Section: Heterojunctionmentioning
confidence: 71%
“…A shift less than −5 cm −1 can be ignored. In the present case the 209 Bi atom is substituted by a 212 Bi, 51 V is substituted by 54 V, and 16 O is substituted by 18 O. The shifts in the peak positions with respect to the isotopic substitution (one at a time) are shown in Fig.…”
Section: Infrared and Raman Spectramentioning
confidence: 99%
“…The shifts in the infrared and Raman modes with respect to isotopic substitution are shown. 51 V is substituted by 54 V, 209 Bi is substituted by 212 Bi, and 16 O is substituted by 18 O. The oscillator strengths are normalized to unity.…”
Section: Infrared and Raman Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…In state-ofthe-arts ystems, metal oxidess uch as a-Fe 2 O 3 , [3] WO 3 , [4] and BiVO 4 [5] have been reported as promising n-type photoanodes for the oxygen evolution half-reaction( OER), whereas the ptype metal oxides CuO [6] and Cu 2 O [7] have been extensively studied as photocathode for the hydrogen evolution half-reaction (HER). [8b] Kalanur et al [13] observed the existence of W 5 + sub-states at the BiVO 4 /WO 3 interface, which led the formation of p-n junction photoelectrodes with enhanced performance for the water oxidation. However, the lowp hotovoltage output of all metal oxide-basedp /n PEC cells (usually < 1V)l imits the unbiased water splitting efficiency.T op rovide sufficient photovoltagea nd enhanced charge separation to drive water splitting, the photoelectrodes must Using dual-photoelectrode photoelectrochemical (PEC) devices based on earth-abundant metal oxides for unbiasedw ater splitting is an attractive means of producing green H 2 fuel, but is challenging,o wing to low photovoltages generated by PEC cells.…”
Section: Introductionmentioning
confidence: 99%